Factors associated with sarcopenia in subjects aged 80 years and over - Santos, Vanessa Ribeiro dos [UNESP] (2015)
ObjectiveTo analyze whether sarcopenia is associated with sociodemographic factors and chronic noncommunicable diseases in adults aged 80 years and older.MethodsThe sample consisted of 120 adults aged 80 to 95 years (83.4 +/- 2.9 years) from the city of Presidente Prudente (Sao Paulo, Brazil), of which 76 were females (83.4 +/- 3.0 years) and 44 were males (83.4 +/- 2.6 years). The study sociodemographic and epidemiological factors were: age stratum, gender, marital status, education level, chronic noncommunicable diseases, ethnicity, and nutritional status. Body composition was determined by Dual-Energy X-Ray Absorptiometry and sarcopenia was identified by the appendicular lean mass ratio (upper limb lean mass + lower limb lean mass [kg]/height [m](2)). The Chi-square test analyzed whether sarcopenia was associated with sociodemographic and epidemiological factors and binary logistic regression expressed the magnitude of the associations. The data were treated by the software Statistical Package for the Social Sciences (17.0) at a significance level of 5%.ResultsThe factors associated with sarcopenia were gender, age, nutritional status, and osteopenia/osteoporosis.ConclusionThe factors gender, age, nutritional status, and osteopenia/osteoporosis are independently associated with sarcopenia in adults aged 80 years and older.